Association between Cuttings Maturity and Alternative Substrates in the Rooting of Acerola Cherry - Eduardo Mendonça Pinheiro; José Ribamar Gusmão Araujo; Camila Pinheiro Nobre; Wallyson Santos Araújo; Altamiro Souza Lima Ferraz Júnior; Mário Luiz Ribeiro Mesquita (Brazilian Archives of Biology and Technology, 2024)
Abstract Vegetative propagation methods of acerola cherry are important in standardizing orchards and fruit quality, and the cutting process has been investigated as a promising alternative. The present work aimed to propose the best combination of substrate and cutting type (herbaceous and semi-woody) to provide a greater root rate and seedling development. The trial was conducted in a greenhouse at the State University of Maranhão, in São Luís - MA under intermittent nebulization conditions. The cuttings with dimensions of 10 cm were treated with indole butyric acid (IBA) at a concentration of 2,000 mg L-1, and as substrate were used vermiculite (MV), Plantmax ® (PL) (commercial substrate based on decomposed pine bark), agricultural soil + tanned and sieved bovine manure (S + M) (50% + 50%, v / v); and vegetable soil (VS) composed of fresh soil with the remains of decomposed plants (leaves, stems, bark, and tree fern). The experiment was laid out in a randomized complete design in a 2 x 4 factorial arrangement (2 types of cuttings x 4 substrates) with eight replications with five cuttings per plot. At 60 days after the establishment of the trial, it was concluded that the best combination for rooting cuttings was vermiculite with herbaceous cuttings because they favor a higher rooting rate (95.0%). The alternative substrate composed of soil and tanned bovine manure provided promising results in the rate of rooting (72.5%), root formation, and vegetative development of the aerial part.